The Effect of Nutrition Education on Student's Consumption Behavior at Universitas Slamet Riyadi Surakarta - Nanik Suhartatik; Diyah Ayu Eka Patmasari; Yustina Wuri Wulandari; Akhmad Mustofa; Sri Handayani (Talenta Publisher, 2020)
The risk of obesity and chronic diseases rises with the increase in one's level of welfare. Among the influencing factors for such phenomenon are eating behavior and lifestyle. Modern lifestyle which demands that everything be done in an instant makes people consume food with the nutritional adequacy disregarded. The emergence of fast food and junk food in Indonesia has also exerted an influence on people's consumption pattern. Some preventive and mitigating efforts can be made, one of which is provision of nutrition education. This research was aimed to determine the influence of nutrition education on the change of consumption knowledge, behavior, and habit of the students of Universitas Slamet Riyadi Surakarta. The respondents enrolled in this research were of the ages of 19-21 years. They were purposively selected on the basis that some of them were able to plan and select which food to be consumed. This research employed questionnaires during pre-test and post-test, with the respondents assigned to 2 groups of 32 students each. The first group received nutrition education, while the second received none. Results showed that the provision of nutrition education for college students didn't influence students' knowledge, attitude, and behavior when consuming food for both groups. The preference of the student college to food consumption probably influenced by another factors. It would need another study to evaluated factors that influenced the food preference of student college.